A positive electrode sheet and its preparation method and application
By realizing the natural gradient distribution of single crystals and polycrystalline materials in the active material layer of the secondary battery positive pole sheet, and using vibration treatment technology to solve the problem of insufficient positive film performance in the existing technology, significantly improves the battery's battery. Overall performance.
Patent Information
- Application Number
- CN202411123813.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-08-15
AI Technical Summary
The existing positive electrode sheet of secondary batteries is difficult to meet the high requirements of compaction density, rate performance, cycle performance and energy density at the same time, and the direct blending of polycrystalline and single crystal materials leads to uneven charging and discharge, and insufficient cycle life.
By realizing the natural gradient distribution of single crystal cathode materials and polycrystalline cathode materials in the cathode active material layer, vibration processing technology is used to promote the material to present a gradient distribution in the cathode plate, thereby improving compaction density, rate performance, cycle performance and energy. density.
The compact density, multiplier performance, cycle performance, and energy density of the positive poles are achieved, avoiding the problem of charging and discharge differences and material separation, and extending the cycle life of the battery.
Smart Images

Figure CN118658962B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology and relates to a positive electrode plate and a preparation method and application thereof. Background Art
[0002] Secondary batteries (lithium-ion secondary batteries or sodium-ion secondary batteries) are increasingly used in our lives due to their excellent performance, but their cycle life still cannot meet people's needs, and the charging rate is still low. The current production methods of secondary battery pole pieces include wet preparation or dry preparation. For the above-mentioned pole pieces, the positive electrode mainly uses polycrystalline materials (secondary balls) or single crystal materials. Polycrystalline materials have the characteristics of good rate performance and high capacity, but their cycle life and high-temperature storage performance are poor. Single crystals have poor rate performance and low capacity, but their cycle performance is good and high-temperature storage is good.
[0003] CN114005955A provides a positive electrode sheet and a preparation method and use thereof. The positive electrode sheet comprises a current collector and an electrode layer, and the electrode layer comprises a ternary single crystal positive electrode material, polytriphenylamine, a conductive agent and a binder. In the process of preparing the positive electrode sheet, polytriphenylamine is added to make the polytriphenylamine composite with the ternary single crystal positive electrode material.
[0004] CN116031379A provides a secondary battery and a preparation method thereof and an electronic device. The secondary battery includes a positive electrode plate, the positive electrode plate includes a positive electrode collector and a positive electrode active material layer, and the positive electrode active material layer is arranged on at least one side of the positive electrode collector; the positive electrode active material layer contains positive electrode active materials, and the positive electrode active materials include polycrystalline nickel cobalt lithium manganese oxide and lithium manganese oxide, wherein the mass proportion of polycrystalline nickel cobalt lithium manganese oxide in the positive electrode active material is 50% to 95%, and the mass proportion of lithium manganese oxide in the positive electrode active material is 5% to 50%.
[0005] The above two documents separately use single crystal materials and polycrystalline materials to prepare positive electrode sheets, which cannot meet the high requirements of compaction density, rate performance, cycle performance and energy density at the same time. If the two materials are directly mixed, the two materials are mixed evenly after mixing. Due to the even mixing, the difference between the two materials themselves during the charge and discharge process leads to microscopic charge and discharge unevenness, which makes the cycle life unable to reach a longer level. Even if a double-layer coating is used, the upper layer is coated with polycrystalline and the lower layer is coated with single crystal, but there is no transition zone between single crystal and polycrystalline, so there is a difference in the charge and discharge of the upper and lower layers, and the two layers are easily separated due to the difference in stress, which cannot solve this problem well.
[0006] CN112151794A provides a positive electrode sheet capable of high-rate discharge and a lithium-ion battery comprising the positive electrode sheet. The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer coated on the first surface of the positive electrode current collector; the positive electrode active material layer comprises a first positive electrode active material and a second positive electrode active material; the first positive electrode active material is a modified or unmodified polycrystalline nickel-containing ternary material, and the second positive electrode active material is a modified or unmodified single crystal or quasi-single crystal nickel-containing ternary material; the document performs uniform mixing of single crystal material and polycrystalline material, and due to the uniform mixing, the difference between the two materials themselves during the charge and discharge process leads to microscopic charge and discharge unevenness, so that the cycle life cannot be extended to a longer level.
[0007] CN114597351A relates to a method for preparing a composite electrode pole piece, wherein a single crystal particle material slurry and a secondary ball particle material slurry of a lithium ion positive electrode are layered and coated on a current collector to prepare a positive electrode pole piece. In this document, a double-layer coating is used, where the upper layer is coated with polycrystalline and the lower layer is coated with single crystal, but since there is no transition zone between the single crystal and the polycrystalline, there is a difference in the charging and discharging of the upper and lower layers, and due to the difference in stress, the two layers are easily separated, and this problem cannot be solved well.
[0008] Therefore, how to make the positive electrode sheet meet the high requirements of compaction density, rate performance, cycle performance and energy density at the same time is a technical problem that needs to be solved urgently. Summary of the invention
[0009] In view of the shortcomings of the prior art, the purpose of this application is to provide a positive electrode sheet and its preparation method and application. The positive electrode sheet provided by this application realizes the natural gradient distribution of single crystal positive electrode material and polycrystalline positive electrode material in the positive electrode active material layer, thereby simultaneously achieving a significant improvement in compaction density, rate performance, cycle performance and energy density.
[0010] In order to achieve the purpose of this application, this application adopts the following technical solutions:
[0011] In a first aspect, the present application provides a positive electrode plate, the positive electrode plate comprising a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector;
[0012] Along the direction away from the positive electrode current collector, the mass proportion of the single crystal positive electrode material in the positive electrode active material layer gradually decreases, and the mass proportion of the polycrystalline positive electrode material in the positive electrode active material layer gradually increases.
[0013] The positive electrode plate provided in the present application, the single crystal positive electrode material and the polycrystalline positive electrode material in the positive electrode active material layer present a naturally transitioned gradient distribution, the single crystal positive electrode material has good cycle performance and good high temperature storage, while the polycrystalline positive electrode material has the advantages of good rate performance and high capacity, so during the charge and discharge process, the upper layer (the position away from the positive electrode current collector in the positive electrode active material layer) with more polycrystalline positive electrode material can show better rate performance, while the lower layer (the position close to the positive electrode current collector in the positive electrode active material layer) with more single crystal positive electrode material shows better storage performance and cycle performance, and at the same time, the naturally transitioned gradient distribution in the present application also avoids the charge and discharge difference in the positive electrode active material layer, and due to the gradient distribution of the single crystal positive electrode material and the polycrystalline positive electrode material, the compaction of the plate is also improved, the stress distribution in the positive electrode active material layer is uniform, and the energy density of the battery cell is higher, thereby achieving a significant improvement in the compaction density, rate performance, cycle performance and energy density of the positive electrode plate.
[0014] The following are preferred technical solutions for this application, but are not intended to limit the technical solutions provided by this application. Through the following preferred technical solutions, the technical objectives and beneficial effects of this application can be better achieved and realized.
[0015] Preferably, in the positive electrode active material layer, the mass ratio of the polycrystalline positive electrode material to the single crystal positive electrode material is (60-95):(5-40).
[0016] The distribution rate of the single crystal positive electrode material in the surface of the positive electrode active material layer close to the positive electrode current collector is 60% to 90%.
[0017] The distribution rate of the polycrystalline positive electrode material in the surface of the positive electrode active material layer away from the positive electrode current collector is 60% to 90%.
[0018] It should be noted that the distribution rate in the present application is defined as: the area occupied by the single-crystalline positive electrode material in any region of the positive electrode material is defined as A, and the area occupied by the polycrystalline positive electrode material in the same region is defined as B. Then the distribution rate of the polycrystalline positive electrode material in the region is B / (A+B), and the distribution rate of the single-crystalline positive electrode material in the region is A / (A+B).
[0019] In a second aspect, the present application provides a method for preparing a positive electrode sheet as described in the first aspect, the preparation method comprising the following steps:
[0020] Arranging an initial positive electrode active material film layer on at least one side of the positive electrode current collector to obtain a positive electrode sheet to be compacted;
[0021] The positive electrode sheet to be compacted is subjected to an up-and-down vibration treatment along the thickness direction of the initial positive electrode active material film layer to compact the positive electrode sheet to obtain the positive electrode sheet;
[0022] The raw materials for preparing the initial positive electrode active material film layer include single crystal positive electrode active materials and polycrystalline positive electrode active materials.
[0023] Preferably, the vibration frequency Z of the vibration treatment and the single-surface density C of the positive electrode plate satisfy: 1≤Z / C≤100.
[0024] Preferably, the vibration frequency of the vibration treatment is 10-2000 Hz.
[0025] The single surface density of the positive electrode sheet is 10-25 mg / cm 2 .
[0026] Preferably, the vibration time t of the vibration treatment, the relative mass ratio P of the polycrystalline positive electrode material and the relative mass ratio S of the single crystal positive electrode material satisfy: P / S≤t≤2P / S, S+P=1, and the unit of t is s.
[0027] It should be noted that the relationship of P / S≤t≤2P / S in the present application satisfies a purely numerical relationship based on the unit of t being s.
[0028] As a preferred technical solution, the preparation method comprises the following steps:
[0029] Arranging an initial positive electrode active material film layer on at least one side of the positive electrode current collector to obtain a positive electrode sheet to be compacted;
[0030] The positive electrode sheet to be compacted is vibrated up and down at a vibration frequency of 10-2000 Hz along the thickness direction of the initial positive electrode active material film layer, and compacted to obtain a single-side surface density of 10-25 mg / cm 2 The positive electrode;
[0031] The raw materials for preparing the initial positive electrode active material film layer include single crystal positive electrode active material and polycrystalline positive electrode active material; the vibration frequency Z of the vibration treatment and the single-surface surface density C of the positive electrode plate satisfy: 1≤Z / C≤100; the vibration time t of the vibration treatment, the relative mass ratio P of the polycrystalline positive electrode material and the relative mass ratio S of the single crystal positive electrode material satisfy: P / S≤t≤2P / S, S+P=1.
[0032] In a third aspect, the present application provides a battery, comprising the positive electrode sheet as described in the first aspect or the positive electrode sheet prepared by the preparation method as described in the second aspect.
[0033] In a fourth aspect, the present application further provides an electrical device, wherein the electrical device comprises the battery as described in the first aspect.
[0034] Compared with the prior art, this application has the following beneficial effects:
[0035] (1) The positive electrode sheet provided by the present application has a naturally transitioned gradient distribution of the content of the single crystal positive electrode material and the polycrystalline positive electrode material in the positive electrode active material layer, wherein the content of the polycrystalline positive electrode material in the positive electrode active material layer gradually increases as it moves away from the current collector, and the content of the single crystal positive electrode material in the positive electrode active material layer gradually decreases as it moves away from the current collector. During the charge and discharge process, there are more polycrystalline positive electrode materials in the upper layer of the sheet (the position in the positive electrode active material layer away from the positive electrode current collector), which helps the sheet have good rate performance, while there are more single crystal positive electrode materials in the lower layer of the sheet (the position in the positive electrode active material layer close to the positive electrode current collector), which helps the sheet have good storage performance and cycle performance. At the same time, the gradient distribution of the single crystal positive electrode material and the polycrystalline positive electrode material also improves the compaction of the sheet, and the continuous and natural gradient also avoids the charge and discharge difference in the positive electrode active material layer. The stress distribution in the positive electrode active material layer in the pole piece provided by the present invention is uniform, and the energy density of the battery cell is higher, thereby achieving a significant improvement in the compaction density, rate performance, cycle performance and energy density of the positive electrode piece.
[0036] (2) The preparation method provided in the present application causes the single crystal positive electrode material to move in the direction close to the positive electrode current collector and the polycrystalline positive electrode material to move in the direction away from the positive electrode current collector by vibrating the positive electrode sheet to be compacted up and down. Finally, the single crystal positive electrode material and the polycrystalline positive electrode material present a naturally transitioned gradient distribution in the positive electrode sheet, which improves the dynamic performance of the positive electrode sheet. The vibration treatment can also reduce the gaps between particles and cooperate with the subsequent compaction process. After compaction, the pores in the positive electrode active material layer become less, and the compaction density is significantly improved. The preparation method provided in the present application is simple to operate, does not require multiple film layer preparations, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a schematic structural diagram of the cross section of the positive electrode sheet provided in Example 1 along the thickness direction.
[0038] Figure 2 This is a SEM image of the cross section of the positive electrode active material layer of the positive electrode sheet provided in Example 1.
[0039] Figure 3 This is a schematic structural diagram of the cross section of the positive electrode sheet provided for Comparative Example 1 along the thickness direction.
[0040] Figure 4 This is a schematic structural diagram of the cross section of the positive electrode sheet provided for Comparative Example 2 along the thickness direction.
[0041] Among them, 1-positive electrode current collector, 2-single crystal positive electrode material, 3-polycrystalline positive electrode material. DETAILED DESCRIPTION
[0042] The technical solution of the present application is further described below through specific implementation methods. Those skilled in the art should understand that the embodiments are only to help understand the present application and should not be regarded as specific limitations of the present application.
[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.
[0044] In the description of the embodiments of the present application, “plurality” means more than two, unless otherwise clearly and specifically defined.
[0045] In a first specific embodiment, the present application provides a positive electrode plate, the positive electrode plate comprising a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector;
[0046] Along the direction away from the positive electrode current collector, the mass proportion of the single crystal positive electrode material in the positive electrode active material layer gradually decreases, and the mass proportion of the polycrystalline positive electrode material in the positive electrode active material layer gradually increases.
[0047] The positive electrode sheet provided by the present application, the content of the single crystal positive electrode material and the polycrystalline positive electrode material in the positive electrode active material layer presents a naturally transitioned gradient distribution, wherein the content of the polycrystalline positive electrode material in the positive electrode active material layer gradually increases as it moves away from the current collector, and the content of the single crystal positive electrode material in the positive electrode active material layer gradually decreases as it moves away from the current collector. During the charge and discharge process, there are more polycrystalline positive electrode materials in the upper layer of the electrode sheet (the position in the positive electrode active material layer away from the positive electrode current collector), which helps the electrode sheet have good rate performance, while there are more single crystal positive electrode materials in the lower layer of the electrode sheet (the position in the positive electrode active material layer close to the positive electrode current collector), which helps the electrode sheet have good storage performance and cycle performance. At the same time, due to the gradient distribution of the single crystal positive electrode material and the polycrystalline positive electrode material, the compaction of the electrode sheet is also improved, and the continuous and natural gradient also avoids the charge and discharge difference in the positive electrode active material layer. The stress distribution in the positive electrode active material layer in the pole piece provided by the present invention is uniform, and the energy density of the battery cell is higher, thereby achieving a significant improvement in the compaction density, rate performance, cycle performance and energy density of the positive electrode piece.
[0048] If the single crystal positive electrode material and the polycrystalline positive electrode material in the positive electrode active material layer are not distributed in a gradient and are directly mixed evenly, the differences between the two materials themselves during the charge and discharge process will lead to microscopic charge and discharge unevenness, and the cycle life cannot be extended to a longer level; and if a technical solution of stacking and distributing the single crystal positive electrode active material layer and the polycrystalline active material layer is adopted, there will be differences in charge and discharge of the upper and lower layers due to the absence of a transition zone between the single crystal positive electrode material and the polycrystalline positive electrode material, and the two layers are likely to separate due to the difference in stress, resulting in the inability to exert the performance synergistically.
[0049] As a preferred technical solution in the first specific implementation manner, in the positive electrode active material layer, the mass ratio of the polycrystalline positive electrode material to the single crystal positive electrode material is (60~95):(5~40), for example, 60:40, 65:35, 70:30, 75:25, 80:20, 85:15, 90:10 or 95:5, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] It should be noted that the mass ratio of the polycrystalline positive electrode material to the single crystal positive electrode material in the present application is (60~95): (5~40), which is also the mass ratio of the raw materials for preparation. That is, after maintaining the above ratio and preparing the positive electrode active material layer, the mass ratio in the product structure will not change.
[0051] As a preferred technical solution in the first specific implementation:
[0052] The distribution rate of the single crystal positive electrode material in the surface of the positive electrode active material layer close to the positive electrode current collector is 60% to 90%, for example, 60%, 65%, 70%, 75%, 80%, 85% or 90%, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0053] and / or,
[0054] The distribution rate of the polycrystalline positive electrode material in the surface of the positive electrode active material layer away from the positive electrode current collector is 60% to 90%, for example, 60%, 65%, 70%, 75%, 80%, 85% or 90%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] It should be noted that the distribution rate in the present application is defined as follows: the area occupied by the single crystal positive electrode material in any region of the positive electrode material is defined as A, and the area occupied by the polycrystalline positive electrode material in the same region is defined as B, then the distribution rate of the polycrystalline positive electrode material in the region is B / (A+B), and the distribution rate of the single crystal positive electrode material in the region is A / (A+B);
[0056] Specifically, the calculation process of the distribution rate is as follows: take the uncompacted electrode sheet and magnify it 1000 times under SEM, draw a square frame of 50~100μm in the SEM image, use Metis software to identify the area occupied by the single crystal positive electrode material and the polycrystalline positive electrode material, and thus calculate the distribution rate of the single crystal positive electrode material and the distribution rate of the polycrystalline positive electrode material;
[0057] Furthermore, the sampling method of the surface of the positive electrode active material layer close to the positive electrode current collector side in the electrode sheet (the surface of the positive electrode active material layer close to the positive electrode current collector is the lower surface, and the surface of the positive electrode active material layer away from the positive electrode current collector is the upper surface) includes: using double-sided tape or 3M tape to stick to the electrode sheet surface, pulling the positive electrode current collector, and tearing the positive electrode current collector and the positive electrode active material layer apart, thereby realizing the testing and calculation of the distribution rate of the positive electrode active material layer close to the positive electrode current collector side.
[0058] In the present application, by regulating the distribution rate of the single crystal positive electrode material in the lower surface or the distribution rate of the polycrystalline positive electrode material in the upper surface to 60~90%, the uneven distribution of polycrystalline and single crystal is ensured. During the charging and discharging process, the polycrystalline is more on the surface and can receive or release lithium ions faster, so that the rate performance is better. The storage and cycle performance of the single crystal at the bottom layer is improved without affecting the rate. At the same time, due to the vibration, the arrangement between the single crystal and polycrystalline particles is closer, which is conducive to the improvement of compaction.
[0059] In a second specific embodiment, the present application provides a method for preparing a positive electrode sheet as described in the first specific embodiment, the preparation method comprising the following steps:
[0060] Arranging an initial positive electrode active material film layer on at least one side of the positive electrode current collector to obtain a positive electrode sheet to be compacted;
[0061] The positive electrode sheet to be compacted is subjected to an up-and-down vibration treatment along the thickness direction of the initial positive electrode active material film layer to compact the positive electrode sheet to obtain the positive electrode sheet;
[0062] The raw materials for preparing the initial positive electrode active material film layer include single crystal positive electrode active materials and polycrystalline positive electrode active materials.
[0063] It needs to be explained that:
[0064] When the electrode to be compacted in the present application is prepared by wet method, it is an electrode that is not dried or rolled after drying, that is, the compaction in the wet method preparation process includes drying first and then rolling;
[0065] When the compacted electrode is prepared by dry method, it is the electrode that has not been compacted (that is, the drying process is not involved), that is, the compaction in the dry preparation process includes hot pressing treatment.
[0066] The preparation method provided in the present application causes the single crystal positive electrode material to move in the direction close to the positive electrode current collector and the polycrystalline positive electrode material to move in the direction away from the positive electrode current collector by vibrating the positive electrode plate to be compacted up and down. Finally, the single crystal positive electrode material and the polycrystalline positive electrode material present a naturally transitioned gradient distribution in the positive electrode plate, which improves the dynamic performance of the positive electrode plate. The vibration treatment can also reduce the gaps between particles and cooperate with the subsequent compaction process. After compaction, the pores in the positive electrode active material layer become less, and the compaction density is significantly improved. The preparation method provided in the present application is simple to operate, does not require the preparation of multiple film layers, and is suitable for large-scale production.
[0067] In the present application, there is no need to vibrate the compacted positive electrode sheet left and right; and if vibration treatment is performed after compaction, the particles in the positive electrode active material layer will be fixed, and even vibration treatment cannot achieve a natural transition gradient distribution between single crystal positive electrode material and polycrystalline positive electrode material.
[0068] As a preferred technical solution in the second specific implementation, the vibration frequency Z of the vibration treatment and the single-sided surface density C of the positive electrode plate satisfy: 1≤Z / C≤100, for example 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95 or 100, etc., but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0069] In the present application, by regulating the vibration frequency Z of the vibration treatment and the single-sided surface density C of the positive electrode plate to satisfy: 1≤Z / C≤100, it is more conducive to the gradient distribution of polycrystalline positive electrode materials and single-crystalline positive electrode materials. When the surface density is large, a larger frequency is required to prompt the particles to move a larger distance. When the surface density is low, a low vibration frequency is required to make the particles move a smaller distance.
[0070] Further, the vibration frequency of the vibration treatment is 10 to 2000 Hz, for example, 10 Hz, 50 Hz, 100 Hz, 200 Hz, 300 Hz, 400 Hz, 500 Hz, 600 Hz, 700 Hz, 800 Hz, 900 Hz, 1000 Hz, 1100 Hz, 1200 Hz, 1300 Hz, 1400 Hz, 1500 Hz, 1600 Hz, 1700 Hz, 1800 Hz, 1900 Hz or 2000 Hz, but is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0071] and / or,
[0072] The single surface density of the positive electrode sheet is 10-25 mg / cm 2 , for example 10mg / cm 2、11mg / cm 2 , 12mg / cm 2 、13mg / cm 2 、14mg / cm 2 、15mg / cm 2 、16mg / cm 2 、17mg / cm 2 、18mg / cm 2 、19mg / cm 2 , 20mg / cm 2 , 21mg / cm 2 , 22mg / cm 2 , 23mg / cm 2 , 24mg / cm 2 or 25 mg / cm 2 The above range is not limited to the listed values, and other values not listed within the above range are also applicable.
[0073] As a preferred technical solution in the second specific implementation, the vibration time t of the vibration treatment, the relative mass ratio P of the polycrystalline positive electrode material and the relative mass ratio S of the single crystal positive electrode material satisfy: P / S≤t≤2P / S, S+P=1, and the unit of t is s.
[0074] It should be noted that the relative mass ratio in the present application is defined as: the total mass of the single crystal positive electrode material and the polycrystalline positive electrode material is 1, and the mass ratio of the single crystal positive electrode material or the polycrystalline positive electrode material in the total mass is the relative mass ratio.
[0075] In the present application, by regulating the vibration time t of the vibration treatment, the relative mass ratio P of the polycrystalline positive electrode material and the relative mass ratio S of the single crystal positive electrode material, the vibration time can be regulated more accurately and a good gradient distribution of the single crystal positive electrode material and the polycrystalline positive electrode material can be achieved.
[0076] As a preferred technical solution in the second specific embodiment, the preparation method comprises the following steps:
[0077] Arranging an initial positive electrode active material film layer on at least one side of the positive electrode current collector to obtain a positive electrode sheet to be compacted;
[0078] The positive electrode sheet to be compacted is vibrated up and down at a vibration frequency of 10-2000 Hz along the thickness direction of the initial positive electrode active material film layer, and compacted to obtain a single-side surface density of 10-25 mg / cm 2 The positive electrode;
[0079] The raw materials for preparing the initial positive electrode active material film layer include single crystal positive electrode active material and polycrystalline positive electrode active material; the vibration frequency Z of the vibration treatment and the single-surface surface density C of the positive electrode plate satisfy: 1≤Z / C≤100; the vibration time t of the vibration treatment, the relative mass ratio P of the polycrystalline positive electrode material and the relative mass ratio S of the single crystal positive electrode material satisfy: P / S≤t≤2P / S, S+P=1, and the unit of t is s.
[0080] It is understandable that:
[0081] The specific material types of the single crystal positive electrode material and the polycrystalline positive electrode material provided in the present application are selected by conventional technology. Preferably, the single crystal positive electrode material and the polycrystalline positive electrode material are positive electrode materials of the same type and type except for the different whiskers.
[0082] Specifically, the present application does not specifically limit the specific material type of the positive electrode material, and the present application is applicable to conventional positive electrode materials that can be used for the preparation of positive electrode sheets and have a single crystal crystal form or a polycrystalline whisker;
[0083] Optionally, the positive electrode material includes a lithium ion positive electrode material or a sodium ion positive electrode material;
[0084] The lithium ion positive electrode material is not limited to at least one of a nickel cobalt manganese oxide positive electrode material, a nickel cobalt manganese aluminum oxide positive electrode material, a nickel cobalt aluminum oxide positive electrode material, a lithium cobalt oxide positive electrode material, a lithium manganese oxide positive electrode material, a nickel manganese oxide positive electrode material or a lithium-rich manganese-based positive electrode material;
[0085] The sodium ion positive electrode material includes but is not limited to sodium-ion Prussian white or sodium-ion layered materials;
[0086] Furthermore, the present application has no particular restrictions on the selection of the positive electrode current collector, as long as it has conductivity and does not cause chemical changes in the battery. Preferably, a metal current collector such as aluminum foil, carbon-coated aluminum foil or composite aluminum foil can be used.
[0087] It should also be noted that the preparation method of the initial positive electrode active material film layer in the present application is also a conventional technical choice, and those skilled in the art can make adaptive selections and adjustments according to actual needs. For example, the preparation method includes wet preparation or dry preparation;
[0088] Specifically, during the wet preparation, the raw materials for preparation may include, in addition to the single crystal positive electrode material and the polycrystalline positive electrode material, a conductive agent, a binder and a solvent. The preparation process includes the following steps:
[0089] The positive electrode material (the sum of the polycrystalline positive electrode material and the polycrystalline positive electrode material): the conductive agent: the binder are mixed in a mass ratio of (80-97): (2-10): (1-10) to obtain a positive electrode slurry with a solid content of 40%-80%, and the positive electrode slurry is applied to the surface of at least one side of the positive electrode current collector to form an initial positive electrode active material film layer to obtain a positive electrode sheet to be compacted;
[0090] After obtaining the positive electrode sheet to be compacted, it is subjected to up and down vibration treatment, drying, and roller pressing (i.e. compaction treatment) to obtain the positive electrode sheet;
[0091] In the dry method preparation, the preparation raw materials may include a conductive agent and a binder in addition to the single crystal positive electrode material and the polycrystalline positive electrode material. The preparation process includes the following steps:
[0092] The positive electrode material (the sum of the polycrystalline positive electrode material and the polycrystalline positive electrode material): the conductive agent: the binder are mixed in a mass ratio of (80-97): (2-10): (1-10), and subjected to a fiberization treatment to fiberize the binder so that the particles can be bonded without adding a solvent. After film formation, the binder is composited to the surface of at least one side of the positive electrode current collector to form an initial positive electrode active material film layer;
[0093] After obtaining the initial positive electrode active material film layer, it is subjected to up and down vibration treatment and hot pressing (i.e. compaction treatment) to obtain the positive electrode sheet;
[0094] Furthermore, the present application does not specifically limit the specific types of conductive agents, binders and solvents, and the present application is applicable to all types of materials that can be used for preparing the electrode sheet;
[0095] Optionally, the conductive agent may include graphite, such as natural graphite or artificial graphite; carbon materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers, such as carbon fibers and metal fibers; conductive tubes, such as carbon nanotubes; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives, etc.;
[0096] The binder comprises at least one selected from the group consisting of polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, styrene-butadiene rubber and fluororubber;
[0097] The compound comprises N-methylpyrrolidone and the like.
[0098] In addition, regardless of whether it is a wet preparation or a dry preparation, during the vibration treatment, the conductive agent will adhere to the surface of the positive electrode material and move together, so the uniform distribution of other raw materials except the positive electrode material in the positive electrode active material layer can still be guaranteed.
[0099] In one embodiment, the present application provides a battery, comprising the positive electrode sheet as described in the first specific embodiment above or the positive electrode sheet prepared by the preparation method as described in the second specific embodiment.
[0100] It should be noted that the present application does not specifically limit the type of battery provided, for example, it may be a lithium-ion battery or a sodium-ion battery;
[0101] In addition, the present application provides a battery, which, in addition to the positive electrode sheet provided above, may also include a negative electrode sheet, an electrolyte and a separator (the separator is optional);
[0102] Optionally, the negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer covering the surface of the negative electrode current collector, and the negative electrode current collector can be the carbon-coated current collector provided in the first aspect;
[0103] The negative electrode active material layer includes a negative electrode binder, a negative electrode active material and a negative electrode conductor.
[0104] The negative electrode binder includes but is not limited to polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), nitrile rubber (NBR), styrene-ethylene-butylene-styrene copolymer (SEBS), styrene-butadiene-styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, lithium alginate, etc. Users can choose according to actual needs, and no specific limitation is made here;
[0105] The negative electrode active material includes but is not limited to graphite, soft carbon, hard carbon, silicon oxygen or silicon carbon, etc. Users can choose according to actual needs, and no specific limitation is made here;
[0106] The negative electrode conductive agent includes but is not limited to conductive carbon black, carbon nanotubes, vapor-grown carbon nanotubes or nano-carbon fibers, etc. Users can choose according to actual needs, and this application does not make specific limitations.
[0107] Optionally, the present application does not specifically limit the type of electrolyte, and any known electrolyte material can be used in the present application without violating the concept of the present application. As an illustrative example, the electrolyte can be a liquid electrolyte, a solid electrolyte, or a mixture of a solid electrolyte and a liquid electrolyte.
[0108] In addition, the electrolyte used in the present application may be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc., which can be used in the manufacture of a secondary battery, but is not limited thereto;
[0109] Specifically, the electrolyte may include an organic solvent and a lithium salt (or a sodium salt);
[0110] Any organic solvent can be used without particular limitation as long as it can serve as a medium through which ions participating in the electrochemical reaction of the battery can move; for example, as the organic solvent, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and E-caprolactone can be used; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (wherein R is a linear, branched or cyclic C2-C20 hydrocarbon group, and may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolane;
[0111] Any compound can be used as the lithium salt without particular limitation, as long as it can provide lithium ions used in the lithium secondary battery, for example, the lithium salt source includes but is not limited to at least one of LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4 or LiCF3SO3, etc.;
[0112] Any compound can be used as the sodium salt without particular limitation, as long as it can provide the sodium ions used in the sodium secondary battery, for example, the sodium salt includes but is not limited to at least one of sodium perchlorate, sodium tetrafluoroborate, sodium hexafluorophosphate, sodium trifluoroacetate, sodium difluorophosphate, sodium tetraphenylborate, sodium trifluoromethylsulfonate, sodium bis(fluorosulfonyl)imide) or sodium bis(trifluoromethylsulfonyl)imide, etc.;
[0113] Further, the electrolyte may be a solid electrolyte, and the solid electrolyte particles may include one or more polymer components, oxide solid electrolytes, sulfide solid electrolytes, halide solid electrolytes, borate solid electrolytes, nitride solid electrolytes, or hydride solid electrolytes;
[0114] Alternatively, the main function of the separator is to separate the negative electrode from the positive electrode and provide a path for the movement of lithium ions (or sodium ions). Any separator can be used without particular limitation, as long as it is a separator commonly used in secondary batteries. In particular, a separator with excellent electrolyte wettability and low resistance to ion movement in the electrolyte is preferred. Specifically, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer and an ethylene / methacrylate copolymer, or a laminated structure having more than two layers thereof. In addition, a typical porous non-woven fabric can be used, for example, a non-woven fabric formed of glass fiber, polyethylene terephthalate fiber, etc. having a high melting point. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used in a single-layer or multilayer structure.
[0115] In one embodiment, the present application further provides an electrical device, which includes the battery as described in the above embodiment.
[0116] Example 1
[0117] This embodiment provides a positive electrode sheet, such as Figure 1 As shown, the positive electrode sheet includes a positive electrode current collector 1 (aluminum foil) and a positive electrode active material layer located on one side of the positive electrode current collector 1;
[0118] Along the direction away from the positive electrode current collector 1, the mass proportion of the single crystal positive electrode material 2 (single crystal NCM811 positive electrode material) in the positive electrode active material layer gradually decreases, and the mass proportion of the polycrystalline positive electrode material 3 (polycrystalline NCM811 positive electrode material) in the positive electrode active material layer gradually increases.
[0119] The preparation method of the positive electrode sheet is as follows:
[0120] (1) Weigh polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) in a ratio of 7:93 and add them to a stirring tank. Stir the mixture until the PVDF is completely dissolved and then take out the glue for later use.
[0121] The positive electrode slurry is prepared according to the ratio of positive electrode material: SP: PVDF = 90:5:5. 15g of polycrystalline positive electrode material and 5g of single crystal positive electrode material are weighed and added into a stirring tank. Then 1.11g of conductive carbon black (SP) is added. Finally, 15.9g of glue is added and stirred to obtain a slurry for use. The solid content of the slurry is 60%;
[0122] (2) Place the aluminum foil on the coating machine, use a 300μm film coater to place it on the aluminum foil, pour the slurry, turn on the equipment for coating, and after coating, the initial positive electrode active material film layer is obtained, and the single-sided surface density C is 15mg / cm 2 , obtaining the positive electrode sheet to be compacted (without drying treatment);
[0123] (3) The electrode to be compacted is placed on a vibration device that vibrates up and down (along the thickness direction of the initial positive electrode active material film layer), and the vibration frequency Z is set to 1000 Hz (the vibration frequency Z and the single-sided surface density C of the positive electrode electrode satisfy: Z / C=66.67), and the vibration time is 5 s (the vibration time t, the relative mass ratio P (0.75) of the polycrystalline positive electrode material and the relative mass ratio S (0.25) of the single crystal positive electrode material satisfy: P / S≤t≤2P / S, that is, 3≤5≤6). After the vibration is completed, the electrode is removed and placed in a 110°C oven for drying (first vibration treatment and then drying treatment), and the electrode is rolled using a pressure of 10T to obtain the positive electrode electrode.
[0124] Example 2
[0125] The difference between this embodiment and Embodiment 1 is that the mass ratio of the polycrystalline positive electrode material to the single crystal positive electrode material in this embodiment is 70:30.
[0126] The rest of the preparation methods and parameters were the same as those in Example 1.
[0127] Example 3
[0128] The difference between this embodiment and embodiment 1 is that the single-surface surface density C in step (2) of this embodiment is about 10 mg / cm 2 ; In step (3), the vibration frequency Z is 10 Hz, and the vibration frequency Z and the single-sided surface density C of the positive electrode sheet satisfy: Z / C=1.
[0129] The rest of the preparation methods and parameters were the same as those in Example 1.
[0130] Example 4
[0131] The difference between this embodiment and embodiment 1 is that the single-surface density C in step (2) of this embodiment is about 20 mg / cm 2 ; In step (3), the vibration frequency Z is 2000 Hz, and the vibration frequency Z and the single-sided surface density C of the positive electrode plate satisfy: Z / C=100.
[0132] The rest of the preparation methods and parameters were the same as those in Example 1.
[0133] Example 5
[0134] The difference between this embodiment and embodiment 1 is that the vibration time in step (3) of this embodiment is 1 s, which does not satisfy the relationship between the vibration time t, the relative mass ratio P of the polycrystalline positive electrode material and the relative mass ratio S of the single crystal positive electrode material of P / S≤t≤2P / S, that is, t<P / S.
[0135] The rest of the preparation methods and parameters were the same as those in Example 1.
[0136] Example 6
[0137] The difference between this embodiment and embodiment 1 is that the vibration time in step (3) of this embodiment is 20 s, which does not satisfy the relationship between the vibration time t, the relative mass ratio P of the polycrystalline positive electrode material and the relative mass ratio S of the single crystal positive electrode material of P / S≤t≤2P / S, that is, t>P / S.
[0138] The rest of the preparation methods and parameters were the same as those in Example 1.
[0139] Example 7
[0140] The difference between this embodiment and embodiment 1 is that the vibration frequency in step (3) of this embodiment is 5 Hz, and the vibration frequency Z and the single-surface density C of the positive electrode sheet satisfy: Z / C=0.33.
[0141] The rest of the preparation methods and parameters were the same as those in Example 1.
[0142] Example 8
[0143] The difference between this embodiment and embodiment 1 is that the vibration frequency in step (3) of this embodiment is 2500 Hz, and the vibration frequency Z and the single-surface density C of the positive electrode sheet satisfy: Z / C=166.67.
[0144] The rest of the preparation methods and parameters were the same as those in Example 1.
[0145] Example 9
[0146] This embodiment provides a positive electrode plate, the positive electrode plate comprising a positive electrode current collector (aluminum foil) and a positive electrode active material layer located on one side of the positive electrode current collector;
[0147] Along the direction away from the positive electrode current collector, the mass proportion of the single crystal positive electrode material (single crystal NCM811 positive electrode material) in the positive electrode active material layer gradually decreases, and the mass proportion of the polycrystalline positive electrode material (polycrystalline NCM811 positive electrode material) in the positive electrode active material layer gradually increases.
[0148] The preparation method of the positive electrode sheet is as follows:
[0149] The positive electrode material (the mass ratio of polycrystalline positive electrode material to single crystal positive electrode material is 75:25) and SP and PTFE are weighed and mixed in a ratio of 90:5:5. After mixing, they are put into a high-speed mixer and mixed and fiberized at 500r / min for 10min. After completion, the particles after fiberization are pulverized at 15mg / cm 2 A layer of fiberized mixed material (initial positive electrode active material film layer) is laid on the aluminum foil to obtain a positive electrode sheet to be compacted;
[0150] The electrode piece to be compacted is placed on a vibration device that vibrates up and down (along the thickness direction of the initial positive electrode active material film layer), the vibration frequency is set to 1000 Hz, the time is 5 s, and after completion, hot pressing is performed to obtain the positive electrode piece.
[0151] Comparative Example 1
[0152] This comparative example provides a positive electrode sheet, such as Figure 3 As shown, the positive electrode sheet includes a positive electrode current collector 1 (aluminum foil) and a positive electrode active material layer located on one side of the positive electrode current collector; the single crystal positive electrode material 2 and the polycrystalline positive electrode material 3 in the positive electrode active material layer are evenly mixed.
[0153] The difference between the preparation method of this comparative example and that of Example 1 is that after obtaining the electrode piece to be compacted, this comparative example does not perform vibration treatment, but directly places it in a 110° C. oven for drying, and uses a 10T pressure to roll the electrode piece to obtain the positive electrode piece.
[0154] The rest of the preparation methods and parameters were the same as those in Example 1.
[0155] Comparative Example 2
[0156] This comparative example provides a positive electrode sheet, such as Figure 4 As shown, the positive electrode sheet includes a positive electrode current collector 1 (aluminum foil) and a single crystal positive electrode active material layer (single crystal positive electrode material 2) and a polycrystalline positive electrode active material layer (polycrystalline positive electrode material 3) stacked in sequence on one side of the positive electrode current collector.
[0157] The preparation method of the positive electrode sheet is as follows:
[0158] (1) Preparation of single crystal positive electrode slurry: Weigh polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) in a ratio of 7:93 and add them to a stirring tank. Stir the mixture until the PVDF is completely dissolved and then take out the slurry for later use.
[0159] The positive electrode slurry is prepared according to the ratio of positive electrode material: SP: PVDF = 90:5:5. 20g of single crystal positive electrode material (single crystal NCM811 positive electrode material) is weighed and added to a stirring tank, and then 1.11g of conductive carbon black (SP) is added, and finally 15.9g of glue is added and stirred to obtain single crystal positive electrode slurry for standby use, wherein the slurry solid content is 60%;
[0160] Preparation of polycrystalline positive electrode slurry: Weigh polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) in a ratio of 7:93 and add them to a stirring tank, start stirring, and take out the slurry after PVDF is completely dissolved for later use;
[0161] The positive electrode slurry is prepared according to the ratio of positive electrode material: SP: PVDF = 90:5:5. 20g of polycrystalline positive electrode material (polycrystalline NCM811 positive electrode material) is weighed and added to a stirring tank, followed by 1.11g of conductive carbon black (SP), and finally 15.9g of glue solution is added and stirred to obtain a polycrystalline positive electrode slurry for standby use, wherein the slurry solid content is 60%;
[0162] (2) Place the aluminum foil on the coating machine, use a 150μm film coater to place it on the aluminum foil, pour in the single crystal slurry, turn on the equipment for coating, and obtain the electrode after coating. Place the electrode in a 110℃ oven to dry for later use
[0163] After the electrode is dried, a 250μm scraper is set on a four-sided coater and polycrystalline slurry is added for coating (coating the polycrystalline positive electrode slurry on the surface of the single crystal positive electrode active material layer), and then dried again. After drying, the electrode is rolled using a 10T pressure to obtain the positive electrode with a single crystal lower layer and a polycrystalline upper layer.
[0164] Pole performance test
[0165] (a) Test of the distribution rate of single crystal positive electrode materials and the distribution rate of polycrystalline positive electrode materials:
[0166] The distribution rate of the positive electrode active material layer in the electrode sheet close to the positive electrode current collector surface (bottom) and away from the current collector surface (surface) is tested respectively;
[0167] The surface sampling method of the positive electrode active material layer near the positive electrode current collector side includes: using double-sided tape to stick the electrode surface, pulling the positive electrode current collector, and tearing the positive electrode current collector and the positive electrode active material layer apart, thereby sampling the surface of the positive electrode active material layer near the positive electrode current collector side;
[0168] The electrode sheets to be compacted (electrode sheets that are not rolled or hot pressed) provided in Examples 1-9 and Comparative Examples 1-2 are subjected to SEM tests (the surface (bottom) of the positive electrode active material layer close to the positive electrode current collector and the surface (surface) away from the positive electrode current collector), and the images are taken at a magnification of 1000 times. A square with a side length of 60 μm is framed on the image using Mites to identify the areas of the single-crystalline positive electrode material and the polycrystalline positive electrode material. The area occupied by the single-crystalline positive electrode material is A, and the area occupied by the polycrystalline positive electrode material is B. The distribution rate of the polycrystalline positive electrode material in this area is B / (A+B), and the distribution rate of the single-crystalline positive electrode material in this area is A / (A+B). The distribution rates of the polycrystalline positive electrode material and the single-crystalline positive electrode material are calculated;
[0169] (b) The compaction density of the final positive electrode sheet.
[0170] The above test results are shown in Table 1.
[0171] Table 1
[0172]
[0173] Figure 2 The SEM image of the cross section of the positive electrode active material layer of the positive electrode plate provided in Example 1 is shown. Combined with the calculation results of the distribution rate in Table 1, it can be shown that the single crystal positive electrode material and the polycrystalline positive electrode material in the present application achieve a gradient distribution along the thickness direction of the positive electrode active material layer.
[0174] [Battery preparation and performance testing]
[0175] Preparation of the battery: The positive electrode sheets provided in Examples 1-9 and Comparative Examples 1-2 were cut into discs with a diameter of 15 mm using a punch in a dry environment. A metal lithium sheet was used as a counter electrode in a glove box, and a ceglar composite membrane was selected as the isolation membrane. An electrolyte was added to assemble a button cell. The electrolyte was an organic solution obtained by mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in a mass ratio of 30:50:20. The concentration of lithium salt (lithium hexafluorophosphate) in the electrolyte was 1.15 mol / L.
[0176] Performance Testing:
[0177] The performance test of the button batteries provided in Examples 1-9 and Comparative Examples 1-2 was performed using the Wuhan Blue Electric CT2001A system;
[0178] (a) Rate performance test: the voltage range is 2.8~4.25V, the charge is 0.5C, and the discharge rates are 1C, 2C, and 3C. The charge and discharge tests are performed to obtain the discharge capacity ratio of 2C / 1C and the discharge capacity ratio of 3C / 1C respectively;
[0179] (b) Cycle performance test: the voltage range is 2.8~4.25V, the charge is 1C, and the discharge rate is 1C, and the charge and discharge cycle test is carried out;
[0180] The performance test results of the above batteries are shown in Table 2.
[0181] Table 2
[0182]
[0183] From Table 1-Table 2, we can get:
[0184] From the data results of Examples 1-4 and Example 9, it can be seen that, regardless of whether it is prepared by a wet method or a dry method, the positive electrode sheet, the single crystal positive electrode material and the polycrystalline positive electrode material provided by the present application all achieve a natural gradient distribution, and the compaction density, rate performance and cycle performance are significantly improved;
[0185] From the data results of Example 1, Example 5 and Example 6, it can be seen that the vibration time t of the vibration treatment, the relative mass ratio P of the polycrystalline positive electrode material and the relative mass ratio S of the single crystal positive electrode material satisfy the following conditions: P / S≤t≤2P / S, which can better achieve the gradient distribution of the single crystal positive electrode material and the polycrystalline positive electrode material. If this condition is not met, the gradient distribution of the single crystal positive electrode material and the polycrystalline positive electrode material will not be obvious, thereby reducing the performance of the battery.
[0186] From the data results of Examples 1, 7 and 8, it can be seen that the vibration frequency Z of the vibration treatment and the single-sided surface density C of the positive electrode plate satisfy: 1≤Z / C≤100, which can better realize the movement of the single-crystalline positive electrode material and the polycrystalline positive electrode material during the vibration process. If this condition is not met, the single-crystalline positive electrode material and the polycrystalline positive electrode material cannot form an effective displacement or the displacement of the two is large, thereby resulting in a decrease in the electrochemical performance of the battery.
[0187] It can be seen from the data results of Example 1 and Comparative Examples 1-2 that, whether the single crystal positive electrode material and the polycrystalline positive electrode material are directly mixed evenly in the same active material layer, or form a layered stacking structure, it is difficult to achieve simultaneous improvement in the compaction density, rate performance and cycle performance, and it is impossible to achieve the performance effect in the present application.
[0188] The applicant declares that the above is only a specific implementation method of the present application, but the protection scope of the present application is not limited thereto. Technical personnel in the relevant technical field should understand that any changes or substitutions that can be easily thought of by technical personnel in the relevant technical field within the technical scope disclosed in the present application are within the protection scope and disclosure scope of the present application.
Claims
1. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector; Along the direction away from the positive electrode current collector, the mass proportion of the single crystal positive electrode material in the positive electrode active material layer gradually decreases, and the mass proportion of the polycrystalline positive electrode material in the positive electrode active material layer gradually increases; the single crystal positive electrode material and the polycrystalline positive electrode material are the same positive electrode material.
2. The positive electrode sheet according to claim 1, characterized in that: In the positive electrode active material layer, the mass ratio of the polycrystalline positive electrode material to the single crystal positive electrode material is (60-95):(5-40).
3. The positive electrode sheet according to claim 2, characterized in that: The distribution rate of the single crystal positive electrode material in the surface of the positive electrode active material layer close to the positive electrode current collector is 60% to 90%; The distribution rate of the polycrystalline positive electrode material on the surface of the positive electrode active material layer away from the positive electrode current collector is 60% to 90%; The distribution rate is defined as follows: the area occupied by the single crystal positive electrode material in any region of the positive electrode material is defined as A, and the area occupied by the polycrystalline positive electrode material in the same region is defined as B. Then the distribution rate of the polycrystalline positive electrode material in the region is B / (A+B), and the distribution rate of the single crystal positive electrode material in the region is A / (A+B).
4. A method for preparing a positive electrode sheet according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: Arranging an initial positive electrode active material film layer on at least one side of the positive electrode current collector to obtain a positive electrode sheet to be compacted; The positive electrode sheet to be compacted is subjected to an up-and-down vibration treatment along the thickness direction of the initial positive electrode active material film layer to compact the positive electrode sheet to obtain the positive electrode sheet; The raw materials for preparing the initial positive electrode active material film layer include single crystal positive electrode active materials and polycrystalline positive electrode active materials.
5. The preparation method according to claim 4, characterized in that: The vibration frequency Z of the vibration treatment and the single-sided surface density C of the positive electrode plate satisfy the following relationship: 1≤Z / C≤100.
6. The preparation method according to claim 4 or 5, characterized in that: The vibration frequency of the vibration treatment is 10~2000Hz; The single surface density of the positive electrode sheet is 10-25 mg / cm 2 .
7. The preparation method according to claim 4, characterized in that: The vibration time t of the vibration treatment, the relative mass ratio P of the polycrystalline positive electrode material and the relative mass ratio S of the single crystal positive electrode material satisfy: P / S≤t≤2P / S, S+P=1, and the unit of t is s.
8. The preparation method according to claim 4, characterized in that: The preparation method comprises the following steps: Arranging an initial positive electrode active material film layer on at least one side of the positive electrode current collector to obtain a positive electrode sheet to be compacted; The positive electrode sheet to be compacted is vibrated up and down at a vibration frequency of 10-2000 Hz along the thickness direction of the initial positive electrode active material film layer, and compacted to obtain a single-side surface density of 10-25 mg / cm 2 The positive electrode; The raw materials for preparing the initial positive electrode active material film layer include single crystal positive electrode active material and polycrystalline positive electrode active material; the vibration frequency Z of the vibration treatment and the single-surface surface density C of the positive electrode plate satisfy: 1≤Z / C≤100; the vibration time t of the vibration treatment, the relative mass ratio P of the polycrystalline positive electrode material and the relative mass ratio S of the single crystal positive electrode material satisfy: P / S≤t≤2P / S, S+P=1, and the unit of t is s.
9. A battery, characterized in that: The battery comprises the positive electrode sheet as described in any one of claims 1 to 3 or the positive electrode sheet prepared by the preparation method as described in any one of claims 4 to 8.
10. An electrical device, characterized in that: The electric device comprises the battery as claimed in claim 9.
Citation Information
Patent Citations
Positive electrode sheet capable of discharging at high rate, and lithium ion battery comprising positive electrode sheet
CN112151794A
Positive pole piece, energy storage device and electric equipment
CN116053408A
Positive electrode active material, positive electrode sheet, secondary battery, and electric device
CN117015872A